Testing patients with non-specific symptoms for antibodies against Borrelia burgdorferi sensu lato does not provide useful clinical information about their aetiology. (December 2015) - Markowicz, M.; Kivaranovic, D.; Stanek, G.
Abstract: The aim of this study was to determine whether patients with antibodies against Borrelia burgdorferi sensu lato or who report a history of erythema migrans (EM) or tick bite are more likely to have non-specific symptoms such as musculoskeletal pain, fatigue, sensory disorder, and headache. The study group comprised 423 subjects with non-specific symptoms tested for antibodies against B. burgdorferi sensu lato between July 2012 and December 2014 because of suspicion of Lyme borreliosis (LB). Of these, 285 were females (67%) and 138 were males (33%); the median age was 53 years (range, 7–89 years). Patients with a confirmed diagnosis of LB and patients with a known underlying disease that could influence the development of the symptoms were excluded from the evaluation. Subjects were assigned to the seronegative group or to one of three seropositive groups, and the history of EM and tick bite was also recorded. Statistical analysis was performed with single chi-square tests of independence and multiple logistic regression models. No differences in the occurrence of non-specific symptoms were observed between patients grouped according to antibody status. A history of EM showed no significant effect on any of the non-specific symptoms. A history of tick bite was weakly correlated with joint pain and joint swelling (p <0.05). In conclusion, it is highly unlikely that the complaints are related to a previous infection with B. burgdorferi sensu lato. The results show that testing patients with non-specific symptoms for antibodies against B. burgdorferi sensu lato in the everyday clinical setting does not provide any useful information about their aetiology.